(untitled) (Darya Ganj, New Delhi, 2000)
Contents of material: Modern library and information center management. Library functions. Financial management. Library leadership. Motivation. Library management planing. Library administration. Library training. Managing the cataloguing. Organisational thought.
Keywords: Information retrieval,Library science,Library management